Feeding habits and length-weight relationship of Acentrogobius viridipunctatus (Cuv. & Val.) from Karachi coast - Hoda, S M Shamsul (Indian Journal of Fisheries, 2011)
Although feeding habits and relativecondition factors of different species of gobiidfishes in relation to habitat, seasons, sizes,maturity stages and sexes have been studied bySueyhiro (1942), Khoo (1966), Mutsaddi andBal (1969), Hesthagen (1971), Shiogaki andDotsu (1977), Hayashi and Goto, (1979) andSarker et al. (1980), but no information isavailable from Pakistan. Hence an attempt hasbeen made to present the details of feedinghabits of Acentrogobius viridipunctatus fromPakistan coast